Identification of Autophagy-Related Gene 7 and Autophagic Cell Death in the Planarian Dugesia japonica - Ma, Kexue; Zhang, Yumei; Song, Gege; Wu, Meng; Chen, Guangwen (Frontiers in Physiology, 2018)
Planarians undergo continuous body size remodeling under starvation or during regeneration. This process likely involves autophagy and autophagic cell death, but this hypothesis is supported by few studies. To test this hypothesis, we cloned and characterized autophagy-related gene 7 (Atg7) from the planarian Dugesia japonica (DjAtg7). The full-length cDNA of DjAtg7 measures 2272 bp and includes a 2082-bp open reading frame encoding 693 amino acids with a molecular weight of 79.06 kDa. The deduced amino acid sequence of DjAtg7 contains a conserved ATP-binding site and a catalytic active site of an E1-like enzyme belonging to the ATG7 superfamily. DjAtg7 transcripts are mainly expressed in intestinal tissues of the intact animals. After amputation, DjAtg7 was highly expressed at the newly regenerated intestinal branch on days 3–7 of regeneration and in the old tissue of the distal intestinal branch on day 10 of regeneration. However, knockdown of DjAtg7 by RNAi did not affect planarian regeneration and did not block autophagosome formation, which indicates that autophagy is more complex than previously expected. Interestingly, TEM clearly confirmed that autophagy and autophagic cell death occurred in the old tissues of the newly regenerated planarians and clearly revealed that the dying cell released vesicles containing cellular cytoplasmic contents into the extracellular space. Therefore, the autophagy and autophagic cell death that occurred in the old tissue not only met the demand for body remodeling but also met the demand for energy supply during planarian regeneration. Collectively, our work contributes to the understanding of autophagy and autophagic cell death in planarian regeneration and body remodeling.